2021
DOI: 10.1007/s43440-021-00295-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exogenous vitamin D on thyroid autoimmunity in euthyroid men with autoimmune thyroiditis and early-onset androgenic alopecia

Abstract: Background Early-onset androgenic alopecia is regarded as the phenotypic equivalent of polycystic ovary syndrome in men. Women with polycystic ovary syndrome are at high risk of autoimmune thyroiditis. The aim of the current study was to investigate whether early-onset androgenic alopecia determines the impact of exogenous vitamin D on thyroid autoimmunity and thyroid function in men with autoimmune thyroiditis. Methods The study included 67 young men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
12
2
Order By: Relevance
“…However, studies focusing on these polymorphisms have shown discrepant results. A meta-analysis of 11 case-control studies has been conducted intending to establish an association between the four polymorphisms and HT susceptibility [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies focusing on these polymorphisms have shown discrepant results. A meta-analysis of 11 case-control studies has been conducted intending to establish an association between the four polymorphisms and HT susceptibility [2].…”
Section: Discussionmentioning
confidence: 99%
“…It causes chronic inflammation of the thyroid tissue, with a condition of hypothyroidism in about 20-30% of patients [1]. Vitamin D plays a role in AIT, as investigated in the past years [2]. Different polymorphisms in Vitamin D receptors (VDR) have an important role in AIT risk [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of thyroid disorders, the rate of depression moderately increases in patients suffering from hypothyroidism [3]. Different polymorphisms of vitamin D receptors highly contribute to the risk development for autoimmune thyroiditis (AIT) [4]. Data from recent research has proved that vitamin D deficiency may cause depression manifestations in the population generally [5].…”
Section: Introductionmentioning
confidence: 99%
“…Various polymorphisms of Vitamin D receptors are considered significant in developing the risk for autoimmune thyroiditis (AIT) [6]. Recently, evidence has emerged that low Vitamin D levels are involved in the manifestations of depression and anxiety in the general population [7].…”
Section: Introductionmentioning
confidence: 99%